FLORA AND FAUNA. MINERAL AND ROW RESOURCES OF UZBEKISTAN. - Teshaboyeva Nafisa Zubaydulla qizi; Abduvahobova Sevara Sobirjon qizi (TADQIQOTLAR.UZ, 2024)
Annotation:Uzbekistan is a landlocked country in Central Asia with a diverse range of natural resources. Its flora and fauna are rich and varied, with over 4,000 species of plants and 700 species of vertebrates. The country is also home to a wealth of mineral and raw resources, including gold, silver, copper, zinc, lead, uranium, natural gas, oil, coal, limestone, gypsum, phosphate, and salt. Uzbekistan is a country with a rich and diverse natural heritage. Its flora and fauna are varied and abundant, and its mineral and raw resources are extensive. These resources play a vital role in the country's economy and contribute to its overall development.